2019
DOI: 10.1136/bmjopen-2018-025415
|View full text |Cite
|
Sign up to set email alerts
|

Screening, diagnosis and care cascade for viral hepatitis B and C in Yaoundé, Cameroon: a qualitative study of patients and health providers coping with uncertainty and unbearable costs

Abstract: ObjectivesTo document patients’ and healthcare professionals’ (HCP) experiences with hepatitis B virus (HBV) and hepatitis C virus (HCV) diagnosis and care, as well as consequences of these infections on patients’ life trajectories in Cameroon, an endemic country in sub-Saharan Africa.DesignQualitative sociological study combining in-depth interviews and observations of medical consultations. Interviews and observations transcripts were thematically analysed according to the following themes: circumstances and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 22 publications
3
41
0
Order By: Relevance
“…The general health of PLHCV in this cohort was poor, likely due to late diagnosis after the onset of liver disease symptoms and in the context of high age and presence of other co-morbidities [13]. Kidney failure and chronic diseases such as diabetes and hypertension are prevalent among older PLHCV with a higher risk of mortality [37,38].…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…The general health of PLHCV in this cohort was poor, likely due to late diagnosis after the onset of liver disease symptoms and in the context of high age and presence of other co-morbidities [13]. Kidney failure and chronic diseases such as diabetes and hypertension are prevalent among older PLHCV with a higher risk of mortality [37,38].…”
Section: Discussionmentioning
confidence: 86%
“…Study participants were recruited among patients already identified through gastroenterology consultation. These patients had usually been diagnosed after presenting with liver-related symptoms or following blood donation [13].…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tertiary impacts: the harms associated with an affected person's response to societal stigma and discrimination. The initial reaction upon a diagnosis of HBV infection is generally one of stress and anxiety about one's own health and future [29][30][31][32][33][34], which continues throughout a chronic infection as an intermittent worry about disease progression and premature death at a young age. Increased health-related fears have been linked to greater knowledge about HBV, particularly of HBV-related complications (e.g., the possibility of liver cancer) [35][36][37][38].…”
mentioning
confidence: 99%
“…The thematical analysis was used to analyze the detailed interview/discussion notes line-by-line based on grounded theory. [26][27][28] The results were presented in aggregate across respondents to protect the identities of the individuals. The final list of recommended indicators was formed through a review of government documents, focus group discussions, and in-depth interviews ( Figure 1).…”
Section: Discussionmentioning
confidence: 99%